2022
DOI: 10.3389/fonc.2022.1038925
|View full text |Cite
|
Sign up to set email alerts
|

SKA1/2/3 is a biomarker of poor prognosis in human hepatocellular carcinoma

Abstract: BackgroundSpindle and kinetochore-associated complex subunits 1–3 (SKA1–3) stabilize the kinetochore-attached spindle microtubules in metaphase. Due to the dysregulation in multiple cancers, SKA1–3 is considered a predictor for the prognosis of the patients. However, the potential clinical applications of SKA1–3, particularly in hepatocellular carcinoma (HCC) prognosis and progression, have completely unknown yet.MethodsFor the analysis of SKA1–3 expression and applications in clinics in HCC patients, several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For instance, Shen et al (2021) have found that miRNA-10a-5p is downregulated in HCC tissues and decreases EMT in HCC cells by targeting spindle and kinetochore-associated complex subunit 1 (SKA1). SKA1 is upregulated in tumors, promoting cancer progression, and has a prognostic value in HCC ( Chen et al, 2018 ; Song et al, 2022 ). Other oncosuppressors are miR-143-3p and miR-139-5p, which repress fibroblast growth factor 1 (FGF1) and Wilms’ tumor 1-associating protein (WTAP).…”
Section: Emt-related Ncrnas Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Shen et al (2021) have found that miRNA-10a-5p is downregulated in HCC tissues and decreases EMT in HCC cells by targeting spindle and kinetochore-associated complex subunit 1 (SKA1). SKA1 is upregulated in tumors, promoting cancer progression, and has a prognostic value in HCC ( Chen et al, 2018 ; Song et al, 2022 ). Other oncosuppressors are miR-143-3p and miR-139-5p, which repress fibroblast growth factor 1 (FGF1) and Wilms’ tumor 1-associating protein (WTAP).…”
Section: Emt-related Ncrnas Mechanisms Of Actionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org 2018; Song et al, 2022). Other oncosuppressors are miR-143-3p and miR-139-5p, which repress fibroblast growth factor 1 (FGF1) and Wilms' tumor 1-associating protein (WTAP).…”
Section: Mirna/mrna Axesmentioning
confidence: 99%
“…In gliomas, SKA1 is implicated in the modulation of the Wnt/β-catenin signaling pathway, cell cycle regulation, and epithelial-mesenchymal transition (EMT) [10] . In human hepatocellular carcinoma, SKA1 is involved in various pathways, including the Fanconi anemia pathway, homologous recombination pathway, spliceosome pathway, DNA replication, and cell cycle signaling pathway [11] . It is evident that the signaling pathways mediated by SKA1 exhibit variations across different types of cancers.…”
mentioning
confidence: 99%